Concise encyclopedia of special education - Reynolds, Cecil R., 1952-; Fletcher-Janzen, Elaine (John Wiley & Sons, 2002)
The Concise Encyclopedia of Special Education, Second Edition is a comprehensive resource for those working in the fields of special education research and practice. Featuring reviews of assessment instruments and teaching approaches, legal issues, overviews of specific learning disabilities, dozens of biographies, and more, this complete desk reference is an indispensable guide for professionals, academics, and students alike. Named an American Library Association Top 25 Reference of the Year in its First Edition, The Concise Encyclopedia serves as an important reference for the education of.